Effects of Type 2 Diabetes on the Regulation of Hepatic Glucose Metabolism. (1st September 2004) - Basu, Ananda; Shah, Pankaj; Nielsen, Michael; Basu, Rita; Rizza, Robert A.
Abstract : Glucose production is inappropriately increased in people with type 2 diabetes both before and after food ingestion. Excessive postprandial glucose production occurs in the presence of decreased and delayed insulin secretion and lack of suppression of glucagon release. These abnormalities in hormone secretion, coupled with impaired insulin-induced suppression of glucose production and stimulation of splanchnic glucose uptake, likely account in large part for the excessive amounts of glucose that reach the systemic circulation for disposal by peripheral tissues following food ingestion. In contrast, when adequate basal insulin concentrations are present, neither glucagon-induced stimulation of glucose production nor glucose-induced suppression of glucose production differs in diabetic and nondiabetic subjects matched for gender, age, and degree of obesity. However, when insulin secretion is defective, lack of suppression of glucagon can cause substantial hyperglycemia by enhancing rates of glucose production. Therefore, normalization of hepatic glucose metabolism in people with type 2 diabetes mellitus likely will require normalization of insulin and glucagon secretion as well as hepatic insulin action.